Estimating Model Forecasting the Price of Chicken Eggs In the City of Bengkulu - Herlena Bidi Astuti; E Fauzi; Wawan Eka Putra; Alfayanti Alfayanti; A Ishak (UNIVED Press, Universitas Dehasen Bengkulu, 2021)
The demand for eggs is always high, but the availability of goods is often not balanced with the availability of products on the market. The imbalance between the demand for eggs and the supply makes the price unstable. Chicken eggs are a food commodity that has variable price fluctuations. . Therefore an estimate of future prices is required. Various models can be used as a method of forecasting egg prices. The study was conducted to determine and test the best forecasting model for the retail price of eggs in Bengkulu City. The retail selling value of chicken eggs in the capital city of Bengkulu Province from early 2010 to May 2020 was used as the main variable to be analyzed. ima price forecasting model used to determine the best model based on the lowest MAD, MSE and MAPE values. The results showed that the best model for predicting the retail price of eggs in Bengkulu City is the ARIMA model because it has the smallest MAPE, MAD and MSE values compared to other models.